Igualdade de gênero na participação do mercado de trabalho formal de Santarém: realidade ou utopia? - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
The labor market has undergone several changes over the years, resinifying the role of women and this has made the understanding of productive development come to be observed by new perspectives. Thus, the objective of this work is to investigate whether there will be convergence towards gender equality in the participation of the Santarém formal labor market. The database was extracted from the General Register of Employees and Unemployed (CAGED), in which information was used on admissions registered in the period from 2004 to 2019. To achieve the objective, we used the Integrated Self-Regressive model of Moving Averages - ARIMA to estimate when the differences in admissions between genders converge to zero. The results indicate that the level of education is an important factor for the growth of women's participation in the formal labor market. Moreover, through the ARIMA model (0, 1, 1) it was possible to estimate, on average, the convergence of gender equality in the formal labor market for November 2037, a more pessimistic scenario for July 2065.
Keywords: Santarém; Arima; Trabalho formal; Igualdade de gênero; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS